Potential Use of Bone Charcoal in the Removal of Antimony and Europium Radioisotopes from Radioactive Wastes - M.W. Abdel Raouf; A.A.M. Daifullah (Adsorption Science & Technology)
Bone charcoal has been shown to be a good sorbent for 124 Sb III and 124 Sb V from liquid organic radioactive wastes and for the retention of 152 Eu III from aqueous wastes. Physical sorption was suggested to be the main mechanism operating for radioantimony isotopes with appreciably higher fixation on the sorbent when loaded from the liquid organic radwaste. In contrast, chemisorption was postulated as the main operating mechanism for 152 Eu III with a higher and irreversible fixation on bone charcoal from a neutral aqueous medium.